Human development - Crandell, Thomas L.; Crandell, Corinne Haines; Vander Zanden, James Wilfrid (McGraw-Hill, 2012)
Provides applications to psychology, health care, social work, education, and family dynamics. This title examines populations at risk and explains how they experience development and why their experience is different